America's Failing Economy and the Rise of Ronald Reagan - Crouse, Eric R. (Springer International Publishing, 2018)
This book examines one of the most important economic outcomes in American history-the breakdown of the Keynesian Revolution. Drawing on economic literature, the memoirs of economists and politicians, and the popular press, Eric Crouse examines how economic decline in the 1970s precipitated a political revolution. Keynesian thought flourished through the presidencies of Lyndon B. Johnson, Richard Nixon, and Gerald Ford, until stagflation devastated American workers and Jimmy Carter's economic policies faltered, setting the stage for the 1980 presidential campaign. Tracking years of shifting public opinion and colorful debate between free-market and Keynesian economists, this book illuminates a neglected era of American economic history and shows how Ronald Reagan harnessed a vision of small government and personal freedom that transformed the American political landscape.